Contested Utopia : Jewish Dreams and Israeli Realities - Rosenstein, Marc, 1946- (Book collections on Project MUSE., 2021)
"The first volume to examine the Jewish state through the lens of Jewish utopian thought from its biblical beginnings to modernity, Contested Utopia illuminates a kaleidoscope of conflicting utopian visions influencing Israel"--